Spatial Distribution and Conservation Strategies of Large Carnivores in Human-Dominated Landscape: A Case Study of Asiatic Black Bear in Jilin, China - Hairong, Du; Xiaoliang, Zhi; Minghai, Zhang; Xiangdong, Ruan; Lee, Tien Ming (Frontiers in Ecology and Evolution, 2022)
Large carnivores maintain the balance of ecosystems. Understanding distribution and population changes are necessary prerequisites for scientific conservation strategy. The east of Jilin Province is the habitat of endangered Amur tiger(Panthera tigris altaica). The Chinese government has focused the monitoring on protecting the Amur tiger. However, little is known about Asiatic black bear (ABB, Ursus thibetanus) distribution, population dynamics in the wild, and protection awareness of local residents in Jilin Province，China. We conducted a integrative survey in mountain areas of eastern Jilin to determine ABB distribution. We explored the drivers of the distribution of ABB in Jilin using logstic regression, we further predicted the habitat suitability and potential suitable habitat of the ABB. Totally, we surveyed 112 grids (15km × 15km) from November 2015 to January 2019. Logistic regression analysis revealed that the main factors driving ABB distribution in Jilin are forest coverage, distance from protected areas, distance from main roads (railways and highways), and distance from water bodies. The results of questionnaire survey showed that the local residents’ understanding of ABB distribution is congruent with our field research. They believed that the number of ABBs has gradually increased in the past ten years. Nevertheless, the local residents have a negative attitude towards the ABBs, which may adversely affect efforts to protect them, possibly leading to more conflicts between humans and bears. Therefore, there is a need to consider ways to change the attitude of the locals through the strengthening of the protection propaganda and advocating management as being critical for the protection of ABBs. Our research provides a scientific basis for future conservation planning. We recommend taking local people’s attitude into consideration during conservation management strategy making to reduce human-bear conflicts and promote the coexistence of humans and bears.